Thirty-day hospital readmissions after augmentation cystoplasty: A Nationwide readmissions database analysis. Issue 6 (December 2018) - Maldonado, Nancy; Michel, Joaquin; Barnes, Kelly
Summary: Introduction: Reducing hospital readmissions is a growing priority for hospitals and clinicians in their efforts to improve quality of care and curtail costs. Augmentation cystoplasty is among the most complex and high-morbidity operations in pediatric urology, with up to 25% of patients experiencing a postoperative complication. However, there is a paucity of literature addressing the incidence and characteristics of hospital readmissions after these procedures. This information may be useful in tailoring perioperative interventions to reduce rehospitalization in this population. Objective: This study sought to determine the rate, causes, risk factors, and costs associated with 30-day readmissions for children undergoing augmentation cystoplasty. Study design: We analyzed the Nationwide Readmissions Database (NRD) for children (≤18 years of age) who underwent augmentation cystoplasty for any indication between 2010 and 2014. Rates, causes, and costs of 30-day readmissions were determined. Multivariate logistic regression was used to identify risk factors for readmission. Results: Among 1873 identified cases, the 30-day readmission rate was 19.6%, with an average cost per readmission of $11, 667. The most common reasons for readmission were gastrointestinal complications (19.6%), urinary tract infections (14.1%), and wound complications (11.2%). The median time to readmission was 13 days (interquartile range 6–19 days). Non-infectious genitourinary complications (e.g. hydronephrosis) ($25, 286) and gastrointestinal complications ($12, 924) led to the costliest readmissions, while dehydration/vomiting ($3739) and fever ($4803) were the least costly. On multivariate regression, the only significant risk factor for readmission was an indication of neurogenic bladder (OR 3.82, 95% CI 1.03–14.20, p  = 0.04). Discussion: We present the first study to capture readmissions with 30 days of discharge to the same or outside hospitals after augmentation cystoplasty. Limitations include inability to separate planned and unplanned readmissions and 30-day follow-up period, which prevented analysis of readmissions caused by late complications. Conclusion: Approximately one in five children undergoing augmentation cystoplasty are readmitted within 30 days. An indication of neurogenic bladder is an independent risk factor, while gastrointestinal complications and urinary tract infections are the most common reasons for readmission.